Deep-learning for conversational speech using semantic textual analysis - Suthakar, Shiny Gladdys (Nanyang Technological University, 2022)
Automatic Speech Recognition (ASR) systems today have a prominent and widespread impact among software applications of different domains. They are usually embedded in the applications to provide user input to the main functionality, hence, acting as the cornerstone of these applications, especially potentially life-saving ones. However, most ASR systems today can only work effectively on formal speech input. They have a lot of room to fully understand speech of colloquial nature.